Mandatory food labeling of trans fat acids: qualitative analysis of the public consultation - Vanessa Fernandes Davies; Patricia Constante Jaime
The objective of this paper is to identify the stakeholders and their contributions to the public consultation carried out with regard to the mandatory trans fat acids food labeling proposal in Brazil. Methodology thematic analysis of the documents. Results 25 stakeholders made suggestions regarding the proposed law, and the majority belonged to the food industry sector. The following issues were raised: lack of knowledge among the consumers about trans fat acids; lack of information about trans fat acids in food composition tables and infrastructure to analyse the trans fat content of foods; voluntary trans fat labelling. Conclusions The stakeholders addressed important issues, such as improving nutritional knowledge among the population. However, few stakeholders linked to consumers took part in the public consultation, which might lead to disproportionate influence of the food industry on the development of future food policies.